Imlementasi Augmented Relity dan Pembelajaran Berbasis Game di Sekolah Dasar Inpres Ndetundora 1 : Penelitian - Yohana Nono; Nining Sariyyah; Anselmus Mema; Agustina Modesta Muna; Nunung Ramadhani Zein; Maria Avila Sina; Maria Avila Sina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
SD Inpres Ndetundora 1 is a public elementary school located in Ndetundora III Village, Ende District, Ende Regency, East Nusa Tenggara. As a school that continuously strives to improve the quality of learning, the need for more engaging and easy-to-understand learning media has become increasingly important. This article discusses the application of Augmented Reality technology combined with game-based learning as an innovative strategy to increase motivation, engagement, and conceptual understanding among elementary school students. This approach was designed through the development of simple mobile-based AR media, the use of educational games as core learning activities, and teacher training in the use of this technology. The implementation of this model is expected to provide a more interactive, concrete, and enjoyable learning experience for students at SDI Ndetundora 1, as well as become an alternative solution in facilitating 21st-century learning in school environments with limited facilities.